The Influence of Return On Assets (ROA), Debt To Assets Ratio (DAR), Proportion of Independent Commissioners and Auditor Change on Financial Report Fraud - Putri Widianti; Dwi Asih Surjandari (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2024)
This study aims to determine the effect of Return On Assets, Debt to Asset Ratio, Proportion of Independent Commissioners and Replacement of Auditors on financial statement fraud. The population used in this study were banking companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2021. Determination of the sample using the purposive sampling method, there were 20 companies that met the sample selection criteria. The data in this study were analyzed using multiple regression analysis using data analysis tools, namely using SPSS v25 software. The results of this study indicate that the variable return on assets has an effect on financial statement fraud. While the variables Debt to asset ratio, proportion of independent commissioners and replacement of auditors do not affect financial statement fraud.